Kant-Nash tax competition - Thomas Eichner; Rüdiger Pethig (Center for Economic Studies and ifo Institute (CESifo), 2019)
In a two-country economy we analyze how tax competition differs from the standard all-Nashian tax competition, if one or both countries are Kantians in Roemer's sense. Kantians are shown to choose a higher tax rate than Nashians for any given tax rate of the other country, which indicates that they seek to mitigate the (Nashian) race to the bottom. We avoid dealing with multiple equilibria by assuming that capital is sufficiently scarce, and we find for symmetric countries that the all-Kantian tax competition is efficient and that the inefficient race to the bottom is weakened in economies with a Nashian and a Kantian. That confirms the intuitive idea that countries following the Kantian categorical imperative avoid or at least soften the socially undesirable impact of (Nashian) self-interest. We also investigate the incentives of opportunistic countries to choose Nashian or Kantian behavior out of self-interest and find that either both governments choose to behave as Kantians or that - under different conditions - the robust Nashian selfinterest supersedes Kantian moral principles such that the inefficient all-Nashian tax competition results.
Keywords: H73; H87; C72; 330; tax competition; best reply; Kantian; Nashian; endogenous behavior selection